PENGARUH PROFITABILITAS, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL DENGAN STRUKTUR AKTIVA SEBAGAI VARIABEL MODERATING - Elyanti Rosmanindar; Nurfitri Martaliah; Retno Wulandari (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
This study aims to determine the effect of profitability, liquidity, and firm size on capital structure with asset structure as a moderating variable. This study uses the independent variable, namely capital structure. The data used in this study is secondary data, namely in the form of financial statements of transportation service companies registered with ISSI of 18 companies during 2016-2021. This research is descriptive with a quantitative approach. The data analysis method used is panel data analysis, model testing, classic assumption test, hypothesis testing, moderating regression analysis. The results of this study indicate that profitability has an effect on capital structure, liquidity has no effect on capital structure, firm size has no effect on capital structure, profitability liquidity and firm size simultaneously have an effect on capital structure, asset structure cannot moderate the relationship between profitability and capital structure, asset structure cannot moderate the relationship between liquidity and capital structure, asset structure cannot moderate the relationship between firm size and capital structure.